FINANCIAL INCLUSION AMONG STUDENTS: THE ROLE OF LITEREACY, TECHNOLOGY, AND SOCIAL CAPITAL - Lesmana, Arief Surya; Ganefi, Hadi Satria; Muttaqien, Dadan Darmawan; Lesmana, Ari; Firmansyah, Muhamad Andhika (Gapenas Publisher, 2025)
Financial inclusion has become a global development agenda, yet in Indonesia a significant gap remains between the level of inclusion and financial literacy. Among young generations, particularly university students, access to financial services is increasing through digital platforms, but effective and responsible utilization is still not fully achieved. This study aims to examine the influence of financial literacy, financial technology, and social capital on financial inclusion among students of the Faculty of Economics and Business, Universitas Kuningan. A quantitative approach was employed using survey data and multiple linear regression analysis. The dependent variable was financial inclusion, while the independent variables included financial literacy, financial technology, and social capital. The findings reveal that all three independent variables have a positive and significant effect on financial inclusion. Among them, financial technology has the strongest impact. The model explains 60.2% of the variance in financial inclusion, indicating a strong explanatory power. The study underscores the importance of integrating behavioural, technological, and social dimensions to strengthen financial inclusion among young people. It contributes to the theoretical framework of the Theory of Planned Behaviour and provides practical implications for policymakers, educators, and financial service providers in promoting inclusive and sustainable financial access